The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/rs70100747
|View full text |Cite
|
Sign up to set email alerts
|

Potential of X-Band TerraSAR-X and COSMO-SkyMed SAR Data for the Assessment of Physical Soil Parameters

Abstract: Abstract:The aim of this paper is to analyze the potential of X-band SAR measurements (COSMO-SkyMed and TerraSAR-X) made over bare soils for the estimation of soil moisture and surface geometry parameters at a semi-arid site in Tunisia (North Africa). Radar signals acquired with different configurations (HH and VV polarizations, incidence angles of 26° and 36°) are statistically compared with ground measurements (soil moisture and roughness parameters). The radar measurements are found to be highly sensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 40 publications
(69 reference statements)
0
26
0
Order By: Relevance
“…Given the robustness of the IEM semi-empirical calibration proposed in Baghdadi et al [10,14] for C-and X-bands SAR data as demonstrated in (e.g., [16,18,20]), the objective is to extend the same approach to L-band in order to improve the SAR backscatter prediction. The prediction error on the radar backscattering coefficients based on a 10-fold cross-validation was estimated for each polarization in order to validate the predictive performance of the calibrated version of the IEM (dataset was randomly divided into 90% training and 10% validation data elements and this procedure was repeated 10 times).…”
Section: Iem Semi Empirical Calibration Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Given the robustness of the IEM semi-empirical calibration proposed in Baghdadi et al [10,14] for C-and X-bands SAR data as demonstrated in (e.g., [16,18,20]), the objective is to extend the same approach to L-band in order to improve the SAR backscatter prediction. The prediction error on the radar backscattering coefficients based on a 10-fold cross-validation was estimated for each polarization in order to validate the predictive performance of the calibrated version of the IEM (dataset was randomly divided into 90% training and 10% validation data elements and this procedure was repeated 10 times).…”
Section: Iem Semi Empirical Calibration Methodologymentioning
confidence: 99%
“…In our database, the roughness parameter rms has been estimated with an accuracy ranging between 5% and 10%, and the L-values with an accuracy ranging between 10% and 20% [20,21]. Low uncertainties on the roughness parameters measurements are obtained for high length and low sampling interval of the roughness profiles.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The study site consists mainly of agricultural fields (cereals) on flat landscape. Soil texture measurements showed a clay percentage between 2.4% and 53.1% and sand percentage between 4.4% and 84.3% [29].…”
Section: Real Datasetmentioning
confidence: 99%
“…The Tunisian study site is situated in the Kairouan plain, in central Tunisia Figure 1). The climate in this region is semi-arid Mediterranean, with an average rainfall of approximately 300 mm/year, characterized by a rainy season lasting from October to May, with the two rainiest months being October and March [29]. The study site consists mainly of agricultural fields (cereals) on flat landscape.…”
Section: Real Datasetmentioning
confidence: 99%